Investigation of early axonal phenotypes in an iPSC-derived ALS cellular model using a microfluidic device - Otomo, Asako; Nishijima, Keiko; Murakami, Yuta; Ishikawa, Mitsuru; Yudahira, Haruka; Shimakura, Kento; Okano, Hideyuki; Aoki, Masashi; Kimura, Hiroshi; Hadano, Shinji (Frontiers in Cellular Neuroscience, 2025)
IntroductionAmyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease caused by the loss of upper and lower motor neurons. Mutations in the FUS/TLS gene have been reported as the second most common mutation in Japanese patients with familial ALS. In recent years, lower motor neurons (LMNs) differentiated from induced pluripotent stem cells (iPSCs) derived from ALS patients have been widely used to analyze the mechanisms of neuronal cell death and degeneration.MethodsIn this study, we developed a microfluidic device designed to observe axonal growth, morphology, and trafficking at high resolution in neurons derived from induced pluripotent stem cells (iPSCs) and tested whether our microfluidic device effectively evaluates neurodegenerative phenotypes. We used iPSCs carrying homozygous FUS/TLS mutations (FUS_H517D) to induce LMNs by expressing NEUROG2, ISL1, and LHX3 under the control of the tetracycline regulation system.Results and discussionsAfter seven days of in vitro differentiation (DIV7), we confirmed that over 95% of iPSCs differentiated into HB9-positive LMNs. Notably, the cell viability of FUS_H517D LMNs was comparable to that of LMNs differentiated from iPSCs without the FUS/TLS mutation at DIV7. However, by DIV14 and DIV21, the viability of FUS_H517D LMNs was notably lower than that of control LMNs, indicating degeneration of FUS_H517D LMNs after differentiation. Using our microfluidic device, we assessed axonal phenotypes in FUS_H517D LMNs. Under oxidative stress conditions, we observed that the axonal length of FUS_H517D LMNs was significantly shorter than that of control cells as early as DIV7, with this axonal growth restriction becoming more pronounced by DIV11. This suggests that axonal growth restriction is an early detectable phenotype in degenerating neurons. Additionally, we examined mitochondrial trafficking within axons in our device, which is often disrupted in degenerative neurons. Our results showed a significant increase in the number of motile mitochondria in FUS_H517D LMNs, with retrograde transport accounting for a large portion of trafficking. Our microfluidic device-based culture and evaluation system using FUS_H517D LMNs offers a valuable ALS cellular model focused on early axonal phenotypes. This approach contributes to the study of molecular mechanisms underlying axonal degeneration in ALS.